SEMPOL ABATI SEBAGAI PRODUK MAKANAN UNTUK PENCEGAHAN STUNTING - Bertalina, Bertalina; Hendrayati, Hendrayati; Sahariah, Sitti; Asikin, Hijrah (NHM PRESS, 2024)
Stunting is a failure to thrive due to the accumulation of nutrient deficiencies that occur from pregnancy to 24 months of age (1.000 Hari Pertama Kehidupan). These deficiencies can inhibit growth and negatively impact child welfare. According to WHO 2022, the stunting rate in toddlers is 22.3%, and according to SKI 2023, the stunting rate in toddlers is 21.5%. Eating foods that contain high protein can be one way to prevent stunting.Determined the most preferred Sempol Abati formulation with chicken liver and red spinach substitution and the nutritional value This research was conducted using an experimental method, namely making Sempol Abati with chicken liver substitution F1 (12%), F2 (14%), F3 (16%) and F4 (18%) and in each formula added 10% red spinach. An organoleptic test using a hedonic test (colour, aroma, taste, texture, and overall acceptance) was conducted with 75 panellists and 1 repetition. The most preferred sempol abati product was then analyzed for fiber by the gravimetric method, iron by the ICP-OES method, and other nutrients by TKPI calculation, determining food cost, and selling price. Data were analyzed univariately using a Likert scale. The most preferred formula was F3 (16%). The nutritional value result based on TKPI Formula R0 E 277.95 kcal, P 8.08 g, L 20.1 g, KH 17.3 g, Fe 1.7 mg and fiber 0.05, while the preferred Sempol Abati formula per serving (40 grams) were E 277.38 kcal, P 8.61 g, L 19.64 g, KH 17.54 g, fiber 0.12 g, and Fe (Fe) 2.01 mg. The selling price per serving (2 pieces = 40 grams) was Rp. 6,000. The most preferred formula was formula F3 with 16% chicken liver substitution and 10% red spinach addition. In further research, it can be noted for minimizing the fishy aroma in the product and testing other nutrients in the laboratory.